Democratic Dissonance: Observing and Accounting by Volunteer Election Officials in Hungary - Zsuzsanna Vargha; Mariann Györke (Sociologica)
We reflect on the ability of democratic institutions to provide accountability, and on the relevance of that accountability. We discuss the democratic observation technology of the election official role in the 2022 Hungarian elections, where a social movement of volunteers served to fill these posts on behalf of the beleaguered opposition. A public scandal ensued after the social media sharing of volunteers' accounts. We reflect on the relationship between first-order and second-order observation, and we show the ethnographic aspect of these accounts and the shifting accountability relations in this dynamic. We conclude with provocations about the problem of managing dissonance through existing democratic institutions.